KIAT MENDIRIKAN USAHA BARU YANG LEGAL DAN MEMPUNYAI KEKUATAN HUKUM (DESA CLEBUNG KECAMATAN BUBULAN KABUPATEN BOJONEGORO) - Heru Ismaya; Neneng Rika Jazilatul Kholidah; Erina Duwi Saputri; Fifi Zuriah; Sely Ayu Lestari (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2022)
The people of Clebung village, Bubulan district, Bojonegoro regency, the majority of whom make a living as farmers, are very enthusiastic about opening new businesses as an additional economic income for their families. This makes a challenge for those who want to set up a new business because it must be supported by various things including capital to support the realization of this intention. The purpose of this community service is to guide the people of Clebung village so that they can establish new legal businesses and have a force of law. The method used a the form of counseling, and discussion, as well as carrying out training. The result of community service is the formation of community enthusiasm that will start a new legal business under the law as an additional effort to improve the family economy.